Exploring the influence of non-cognitive skills on academic achievement in STEM education: the case of Kazakhstan - Sultanova, Gulbakhyt; Shilibekova, Aidana; Rakhymbayeva, Zamira; Rakhimbekova, Assel; Shora, Nurym (Frontiers in Education, 2024)
This exploratory study delves into the relationships between non-cognitive skills and academic achievement within the unique context of STEM schools in Kazakhstan. Arising from a survey-based investigation of 109 teachers and 395 students at one STEM school, the study scrutinizes the impact of these skills on the performance in the domains of Mathematics, Computer Science, Physics, and Chemistry. The results showed that out of the 26 skills, eight had a direct impact, 12 had an indirect impact, and six had no impact on academic achievement of students in the four STEM subjects. This study is the first to explicitly examine the impact of one group of non-cognitive skills on academic achievement of students in STEM subjects mediated by another group of these skills. Educators Teachers are encouraged to integrate non-cognitive skill development into curricula, tailored to subject-specific needs. Policymakers can use findings to inform equitable skill development policies.